ELABORASI DAN NILAI-NILAI MANAJEMEN HINDU DALAM ORGANISASI MODERN - Anak Agung Sagung Kartika Dewi; Ni Wayan Mujiati; Anak Agung Sriathi (Forum Manajemen STIMI Handayani Denpasar, 2017)
Management as the art of organization has evolved. Constantly with the spirits of time. Considering that the organization also suffered at the level of structure and culture, Hindu as the first religion in the worldd was having management concepts and theories that should be explored deeply and the next should be elaboration in present context. The consistency between Hindu management and latest management theory could be a theoretical and practical dialogue.